Bacterial versus fungal laccase: potential for micropollutant degradation - Margot, Jonas (Springer, 2013)
Relatively high concentrations of micropollutants in municipal wastewater treatment plant (WWTP) effluents underscore the necessity to develop additional treatment steps prior to discharge of treated wastewater. Microorganisms that produce unspecific oxidative enzymes such as laccases are a potential means to improve biodegradation of these compounds. Four strains of the bacterial genus Streptomyces (S. cyaneus, S. ipomoea, S. griseus and S. psammoticus) and the white-rot fungus Trametes versicolor were studied for their ability to produce active extracellular laccase in biologically treated wastewater with different carbon sources. Among the Streptomyces strains evaluated, only S. cyaneus produced extracellular laccase with sufficient activity to envisage its potential use in WWTPs. Laccase activity produced by T. versicolor was more than 20 times greater, the highest activity being observed with ash branches as the sole carbon source. The laccase preparation of S. cyaneus (abbreviated L(Sc)) and commercial laccase from T. versicolor (L(Tv)) were further compared in terms of their activity at different pH and temperatures, their stability, their substrate range, and their micropollutant oxidation efficiency. L(Sc) and L(Tv) showed highest activities under acidic conditions (around pH 3 to 5), but L(Tv) was active over wider pH and temperature ranges than L(Sc), especially at near-neutral pH and between 10 and 25°C (typical conditions found in WWTPs). L(Tv) was also less affected by pH inactivation. Both laccase preparations oxidized the three micropollutants tested, bisphenol A, diclofenac and mefenamic acid, with faster degradation kinetics observed for L(Tv). Overall, T. versicolor appeared to be the better candidate to remove micropollutants from wastewater in a dedicated post-treatment step.